2019
DOI: 10.1016/j.ajhg.2019.09.024
|View full text |Cite
|
Sign up to set email alerts
|

RPL13 Variants Cause Spondyloepimetaphyseal Dysplasia with Severe Short Stature

Abstract: Variants in genes encoding ribosomal proteins have thus far been associated with Diamond-Blackfan anemia, a rare inherited bone marrow failure, and isolated congenital asplenia. Here, we report one de novo missense variant and three de novo splice variants in RPL13, which encodes ribosomal protein RPL13 (also called eL13), in four unrelated individuals with a rare bone dysplasia causing severe short stature. The three splice variants (c.477þ1G>T, c.477þ1G>A, and c.477þ2 T>C) result in partial intron retention,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 20 publications
2
38
1
Order By: Relevance
“…For those five core RPs with the lowest similarity levels across vertebrates—namely: RPL14/eL14, RPL6/eL6, RPL36/eL36, FAU/RPS30-precursor/eS30 and RPL7/uL30—there is a lack of murine knockout phenotypes ( 82 ); however, they are implicated in the generation of Minute phenotypes in fruit fly ( 83 ). RPL13/eL13, at ∼80% identity between human and zebrafish presents a missense and three splice variants, the latter leading to an 18 aa insertion, with RPL13/eL13 being the cause of a rare ribosomopathy, characterized by skeletal dysplasia ( 84 ). Furthermore, RPL13/eL13 was discovered to be a candidate disease gene in patients with congenital heart disease, with heart-specific RPL13/eL13 knockdowns compromising embryonal heart development in fruit fly ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…For those five core RPs with the lowest similarity levels across vertebrates—namely: RPL14/eL14, RPL6/eL6, RPL36/eL36, FAU/RPS30-precursor/eS30 and RPL7/uL30—there is a lack of murine knockout phenotypes ( 82 ); however, they are implicated in the generation of Minute phenotypes in fruit fly ( 83 ). RPL13/eL13, at ∼80% identity between human and zebrafish presents a missense and three splice variants, the latter leading to an 18 aa insertion, with RPL13/eL13 being the cause of a rare ribosomopathy, characterized by skeletal dysplasia ( 84 ). Furthermore, RPL13/eL13 was discovered to be a candidate disease gene in patients with congenital heart disease, with heart-specific RPL13/eL13 knockdowns compromising embryonal heart development in fruit fly ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we identified de novo mutations responsible for the expression of abnormal variants of the 60S subunit protein RPL13 (eL13). These proteins are efficiently integrated, giving “mutated” ribosomes responsible for severe bone defects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…RPL13 , another gene involved in this duplication, code for a protein incorporated in the 60S subunit of ribosomes, and was very recently described by Le Caignec et al to be associated with a human ribosomopathy, Isidor-Toutain spondyloepimetaphyseal dysplasia, an autosomal dominant disorder ( 27 ). These authors showed that RPL13 gene is highly expressed in osteoblasts and chondrocytes from hypertrophic and remodeling zones in mouse growth plate ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…RPL13 , another gene involved in this duplication, code for a protein incorporated in the 60S subunit of ribosomes, and was very recently described by Le Caignec et al to be associated with a human ribosomopathy, Isidor-Toutain spondyloepimetaphyseal dysplasia, an autosomal dominant disorder ( 27 ). These authors showed that RPL13 gene is highly expressed in osteoblasts and chondrocytes from hypertrophic and remodeling zones in mouse growth plate ( 27 ). RPL13 gene duplication is not known to be associated with human disorder, but the high RPL13 expression in bones and the association with a skeletal dysplasia in case of heterozygous splice variant could have a role for the very low bone density seen in the present case ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation